Strengthening Public Expenditure Efficiency : Investment and Social Spending in Bulgaria - Hallaert, Jean-Jacques (IMF Working Papers; Working Paper ;, 2022)
The scope for increasing public spending to meet Bulgaria's development needs is limited by low revenue. Increasing the efficiency of spending is, therefore, crucial. This paper discusses how this can be achieved in four areas (public investment, social protection, health, and education). The methodology is based on a triple benchmarking. First, the level of public expenditure in each category is compared to other European countries. Second, the impact of spending is assessed against other European countries. Third, the input mix is analyzed to understand what components are responsible for the level of spending and for the quality of outcomes. Based on these results, the paper provides policy options for expenditure reform.